Literasi Sertifikasi Halal Guna Menunjang Percepatan Berkembangnya Usaha Mikro, Kecil, dan Menengah - Soeharjoto, Soeharjoto; Tajib, Erny; Gazali, Masfar; Tribudhi, Debbie Aryani; Jumali, Endang; Putri, Alisa Noviani (Journal Of Human And Education (JAHE), 2025)
The enactment of Article 4 of Law No. 33 of 2014 in 2024 in Indonesia, resulted in micro, small and medium enterprises being required to have a halal certificate. This policy brings significant changes to business operators, because if they cannot fulfil their obligations will result in sanctions in the form of a ban on the circulation of their products in Indonesian territory.This Community Service aims to enhance partners’ knowledge and understanding of halal certification. However, to achieve more optimal results, the partners are also provided with materials on the impact of halal certification on the acceleration of business growth and development. This activity was conducted using the counselling method to micro, small, and medium enterprises at Azalea Grand Depok City. This Community Service has been carried out successfully, as it was able to increase the partners’ knowledge and understanding of consumption, halal products, and welfare by an average of 87.67 percent.In the next implementation, the duration of the meeting should be longer and continuous with a theme that can improve business with Islamic behaviour, as well as conducting comparative studies to business centres that apply Islamic principles.